Effect of a new phosphorus source, magnesium hydrogen phosphate (MHP) on growth, utilization of phosphorus, and physiological responses in carp Cyprinus carpio. Issue 1 (December 2016) - Yoon, Tae-Hyun; Won, Seunggun; Lee, Dong-Hoon; Choi, Jung-Woo; Ra, Changsix; Kim, Jeong-Dae
Abstract Magnesium hydrogen phosphate (MHP, MgHPO4 ) recovered from swine manure was prepared as an alternative phosphorus (P) source. Conventional P additives, monocalcium phosphate (MCP), dicalcium phosphate (DCP), and tricalcium phosphate (TCP) were compared with the MHP in terms of growth and P availability by juvenile carpCyprinus carpio . A basal diet as a negative control was prepared using practical feed ingredients without P supplementation to which four supplemental P sources were added at the level of 2%. Five groups of 450 fish having mean body weight of 6.5 g following 24 h fasting after 2 weeks of adaptation period were randomly distributed into each of 15 tanks (30 fish/tank). Fish were hand-fed to apparent satiety twice a day for 9 weeks. Fish fed the MHP had weight gain (WG), feed conversion ratio (FCR), protein efficiency ratio (PER), and specific growth rate (SGR) comparable to those fed the MCP. Those values of both the MHP and MCP groups were significantly different (p  < 0.05) from the other groups. Fish groups fed control and the TCP showed the lowest WG, PER, and SGR and the highest FCR among treatments. No fish were died among treatments during the experimental period. Fish fed control and the TCP showed hematocrit and hemoglobin significantly lower (p  < 0.05) than fish fed the MHP. The lowest inorganic P (Pi) in plasma was found in the control group. Even though Pi was not significantly different (p  > 0.05) from other phosphate groups, fish fed the MCP and MHP retained higher P in whole body than the other groups. P availability was determined to be 93.2, 62.4, 6.1, and 98.0% for MCP, DCP, TCP, and MHP, respectively. The present results suggested that the MHP recovered from wastewater stream could be used as an alternative P source in carp diet.